ChemInform Abstract: Azodicarbonyl Dimorpholide (ADDM): An Effective, Versatile, and Water‐Soluble Mitsunobu Reagent. Issue 52 (24th December 2013) - Lanning, Maryanna E.; Fletcher, Steven
Abstract The title reagent facilitates the dehydrative coupling of alcohols to various pro‐nucleophiles.